ANALISIS JENIS PIGMEN DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK PIGMEN XANTOFIL PADA ALGA COKLAT Sargassum polycystum (C.Agardh) - Paransa, Darus S. J.; Kemer, Kurnia; Rumengan, Antonius P.; Mantiri, Desy M. H. (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2014)
The separation of algae extracts in a Thin Layered Chromatography used Matsjeh method, covering plate preparation, sample application, plate development and visualization. In addition, the pigment types of brown algae, Sargassum Polycystum (C. Agardh), were Î²-caroten, pheofitine, chlorophyll-a and lutein. The pigment types of extracts dissolved difference were Î²-caroten, xanthofil (zeaxanthin and lutein), chlorophyll-a and chlorophyll-c. The antibacterial activity test used Kirby-Bauer method. Results indicated that the extracts of S. Polycystum, had antibacterial activity on four test bacteria, Escherichia coli, Klebsiella pneumonia, Salmonella paratiphy b and Staphylococcus aureus.Kata Kunci: Algae, Sargassum Polycystum, pigment and antibacterial